Essential Roles of Heparin‐Binding Epidermal Growth Factor‐Like Growth Factor in the Brain - Oyagi, Atsushi (CNS Neurosci Ther, 2012)
Heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF) is a member of the EGF family of growth factors, which interacts with the EGF receptor to exert mitogenic activity for various types of cells. Through its interactions with various molecules, it is involved in diverse biological processes, including wound healing, blast implantation, and tumor formation. At the same time, HB‐EGF is widely expressed in the central nervous system, including the hippocampus and cerebral cortex, and is considered to play pivotal roles in the developing and adult nervous system. Because HB‐EGF protein levels in the brain are much higher than those of TGF‐α and EGF, it is possible that HB‐EGF serves as a major physiologic ligand for the EGF receptor (ErbB1) within the central nervous system. Recent studies indicate that HB‐EGF contributes to the neuronal survival and proliferation of glial/stem cells. HB‐EGF also promotes the survival of dopaminergic neurons, an action mediated by mitogen‐activated protein kinase (MAPK) as well as by the Akt signaling pathway. In this review, we discuss recent findings on the implications of HB‐EGF in higher brain functions of the central nervous system.